Plant-based milk substitutes: sources, production, and nutritional, nutraceutical and sensory qualities - Emmanuel Anyachukwu Irondi; Hope Tomiloba Aina; Yunus Temitayo Imam; Yunus Temitayo Imam; Abigael Odunayo Bankole; Arinze Favour Anyiam; Abdulazeez Olamilekan Elemosho; Babajide Kareem; Titilayo Oluwayemisi Adewumi (Frontiers in Food Science and Technology)
Over the years, humans and the dairy industry have depended mainly on animals, especially cattle, for their milk need. Whether for direct consumption or for the production of value-added dairy products, animal milk seems to be the gold standard, leading to a rise in its price. The exorbitant cost of dairy milk and products, coupled with the susceptibility of some consumers to lactose intolerance, necessitates finding non-dairy milk substitutes to meet human nutritional needs. Thus, to ensure a sustainable food system, in which milk is provided sufficiently and affordably for all, recent studies have demonstrated that plant-based milk substitutes (PBMS) can serve as an alternative to dairy milk in human nutrition. PBMS are prepared from different edible plant sources, including cereals, legumes, nuts, corms, roots and tubers, fruits, and vegetables. Studies have also shown that they are rich sources of nutrients and nutraceuticals, capable of nourishing the body and providing some health benefits. Bioactive compounds, including bioactive peptides, polyphenolics compounds, flavones, and anthocyanins have been reported in PBMS. These bioactive compounds are thought to confer certain health advantages, such as antidiabetic and antihypertensive effects. The sensory qualities of different PBMS have also been reported. The aim of this review was to discuss PBMS in human nutrition, emphasizing their sources, production, and nutritional, nutraceutical and sensory qualities.